2017
DOI: 10.1186/s13048-017-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oocytes with CLCG on ICSI outcomes and their potential relation to pesticide exposure

Abstract: BackgroundOocyte quality is a key limiting factor in female fertility which is primarily reflected in morphological features. Centrally located cytoplasm granulation (CLCG) is one type of cytoplasmic dimorphism exhibited by oocytes that could be linked to pesticide exposure with a significant risk of decreased ICSI outcomes.MethodsThis retrospective study included 633 women who were part of an intracytoplasmic spermatozoa injection (ICSI) program between 2009 and 2011. The participants lived in the Picardy reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 55 publications
2
27
0
1
Order By: Relevance
“…Studies 4,6 have found that central granulation of oocytes had a negative effect on development potential, but this study, through stratified analysis, at least indicated that there was no difference in clinical outcomes between patients with BMI < 24 (Table 3). In the comparative analysis of the study subjects, age and BMI were found to be the interfering factors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Studies 4,6 have found that central granulation of oocytes had a negative effect on development potential, but this study, through stratified analysis, at least indicated that there was no difference in clinical outcomes between patients with BMI < 24 (Table 3). In the comparative analysis of the study subjects, age and BMI were found to be the interfering factors.…”
Section: Discussionmentioning
confidence: 60%
“…Merviel et al . found that some patients had central granules in some oocytes, among which patients with high ratios (>75%) of CLCG compared to lower proportions showed a reduction in cleavage rate, pregnancy rate, and birth rate 4 . Patients exposed to the pesticide environment were found to have an increased incidence of central granulation of oocytes.…”
Section: Introductionmentioning
confidence: 96%
“…This was presumably due to a dysregulated intra-ovarian microenvironment that, during oocyte maturation, affects oocyte morphology with consequent impairment of clinical outcome. The author opted to use ICSI to be able to "read" the oocytes' cytoplasm and overcome the CLCG, granting fertilization [179]. Similarly, other studies confirm ICSI as the preferential tool to inseminate oocytes that require detailed evaluation of their morphological features [180][181][182][183].…”
Section: Zona Pellucida Abnormalitiesmentioning
confidence: 99%
“…Indeed, we have highlighted ( 50 ) a conclusive link between a high prevalence (>75%) of oocytes with centrally located cytoplasm granulation (CLCG) and the patients’ exposure to pesticides in the highly agricultural Picardy area of northern France (annual pesticide consumption: ~3900 tons). As a result, ongoing pregnancy and live birth rates were lower in couples with a high prevalence of oocytes with CLCG than in couples with low (<25%) prevalence (14% vs 32% for the ongoing pregnancy rate and 13% vs 30% for the live birth rate, respectively).…”
Section: Pesticide Exposure and Female Fertilitymentioning
confidence: 99%
“…Women who consume high levels of pesticide residues in fruits and vegetables ( 74 ) or who live in an area with high pesticide exposure ( 50 , 75 ) have an above-average risk of miscarriage. In one study, the probability of clinical pregnancy was 18% below average and the live birth rate was 26% below average in the women most exposed to pesticides ( 74 ).…”
Section: Pesticide Exposure and Female Fertilitymentioning
confidence: 99%